Crystal structure of hydroxy scandium nitrate chloride - Sears, Jeremiah (Acta Crystallogr E Crystallogr Commun, 2019)
Each Sc(3+) ion in the title salt, di-μ-hydroxido-bis[triaqua(nitrato-κ(2) O,O′)scandium(III)] dichloride, [Sc(2)(NO(3))(2)(OH)(2)(H(2)O)(6)]Cl(2), is coordinated by a nitrate anion, two hydroxide ions and three water molecules to generate a distorted pentagonal–bipyramidal ScO(7) coordination polyhedron. The complete {[(NO(3))(μ-OH)Sc(H(2)O)(3)](2)}(2+) ion is generated by crystallographic inversion symmetry. The nitrate anion binds in a bidentate fashion whereas the hydroxide ions are bridged between two Sc centers. Two charge-balancing Cl(−) ions are located in the outer sphere. In the extended structure, O—H⋯O and O—H⋯Cl hydrogen bonds connect the components into a three-dimensional network.